Lung ultrasound pattern in pulmonary tuberculosis - Idris, Nafisah (2020)
Background Pulmonary tuberculosis is a lethal transmissible airborne disease. There are various challenges in establishing diagnosis due to the low sensitivity of conventional bacteriological confirmation and limited accessibility to chest X-ray. These challenges result in a delay of diagnosis, risking more populations being infected, resulting in overall poor control of the disease. We aim to increase the diagnostic accuracy by introducing the usage of lung ultrasound in combination with current diagnostic modalities. We describe common lung ultrasound pattern seen in pulmonary tuberculosis and measure its agreement with the routine screening imaging, that is chest X-ray. Methods A multicenter prospective cross-sectional study was conducted among confirmed pulmonary tuberculosis patients aged above 18 years old. Lung ultrasound was performed using a convex probe covering 14 lung sectors that covered the anterior, lateral and posterior aspect of the lung. The pattern observed in pleura, subpleural and subcostal space were described. The findings were also being compared with chest X-ray to find the agreement between the two imaging modalities. Findings A total of 141 patients were recruited between January 2019 and February 2020. The most frequent sector with findings was R1a seen in 92 (65.4%) patients, followed by R1b seen in 88 (62.4%) patients. The most common zone with finding was right middle zone observed in 112 (79.4%) patients. Pleural irregularity and subpleural consolidation were observed in 139 (98.6%) and 125 (88.7%), respectively. There was a moderate Kappa agreement between lung ultrasound and chest X-ray observed in all zones with a value ranging from 0.46 to 0.59, with higher sensitivity observed for lung ultrasound. Conclusion The lung ultrasound pattern observed is in line with pulmonary tuberculosis pathology, which involved the right upper and middle sector of the lung parenchyma. Lung ultrasound showed higher sensitivity compared to chest X-ray especially when involving right middle zone and right lower zone.